Hiemenz Flow Over A Shrinking Sheet In A Hybrid Nanofluid - Ishak, Anuar; Waini, Iskandar; Pop, Ioan Mihai (Elsevier, 2020)
This study investigates the Hiemenz flow of hybrid nanofluid over a shrinking sheet. The similarity equations are obtained using similarity variables and then solved using the bvp4c solver. The outcomes showed that dual solutions occur for the shrinking case, in the range of 1.24657 1.1 < with c = 1.24657 is the point of bifurcation between the solutions. Meanwhile, the solution is unique for > 1.1. Besides, the heat transfer rate is intensified with the rise of hybrid nanoparticles. Moreover, as hybrid nanoparticles increases, the friction on the surface is increased for < 1, while it is decreased for > 1, and no friction occurs when = 1. Finally, these solutions are tested using the stability analysis where the outcomes found that the first solution is stable and acceptable.